2016
DOI: 10.1039/c5cp04984a
|View full text |Cite
|
Sign up to set email alerts
|

Deducing CO2motion, adsorption locations and binding strengths in a flexible metal–organic framework without open metal sites

Abstract: Microporous metal-organic frameworks (MOFs) have high surface areas and porosities, and are well-suited for CO2 capture. MIL-53 features corner-sharing MO4(OH)2 (M = Al, Ga, Cr, etc.) octahedra interconnected by benzenedicarboxylate linkers that form one-dimensional rhombic tunnels, and exhibits an excellent adsorption ability for guest molecules such as CO2. Studying the behavior of adsorbed CO2 in MIL-53 via solid-state NMR (SSNMR) provides rich information on the dynamic motion of guest molecules as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
120
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 57 publications
(127 citation statements)
references
References 68 publications
4
120
3
Order By: Relevance
“…CO 2 dynamics in MOFs without OMSs, such as MIL‐53(Al, Ga)‐ np and MIL‐53‐NH 2 (Al, Ga)‐ np , have also been studied . In these two cases, static VT 13 C experiments revealed that CO 2 undergoes a localized wobbling about the hydroxyl groups on the linker and a two‐fold hopping between adjacent hydroxyl sites (Figure ).…”
Section: Carbon Dioxide (Co2)supporting
confidence: 90%
See 4 more Smart Citations
“…CO 2 dynamics in MOFs without OMSs, such as MIL‐53(Al, Ga)‐ np and MIL‐53‐NH 2 (Al, Ga)‐ np , have also been studied . In these two cases, static VT 13 C experiments revealed that CO 2 undergoes a localized wobbling about the hydroxyl groups on the linker and a two‐fold hopping between adjacent hydroxyl sites (Figure ).…”
Section: Carbon Dioxide (Co2)supporting
confidence: 90%
“…CO 2 dynamics in MOFs without OMSs, such as MIL-53(Al, Ga)-np and MIL-53-NH 2 (Al, Ga)-np,h ave also been studied. [16] In these two cases, static VT 13 Ce xperiments revealed that CO 2 undergoes al ocalized wobbling aboutt he hydroxyl groups on the linker and at wo-fold hopping between adjacent hydroxyl sites ( Figure 2). As compared to MIL-53,s maller wobbling angles, a,w ere observed for MIL-53-NH 2 .T his indicates ad ecrease in dynamics and thus an increase in CO 2 -MOF interaction, consistent with previouso bservations that amine functionalization can enhanceC O 2 capturea bility.…”
Section: Carbon Dioxide (Co 2 )mentioning
confidence: 93%
See 3 more Smart Citations